Sulear la filosofía: entre utopías y práxis: un camino de Zea a Dussel - Leal, Rayane Ancelmo (2020)
This research aims at presenting a reflection upon the Latin American (Americanista) philosophical thought – its utopias and possible practices within its precursors’s philosophical perspectives. It has a paramount importance due to the relevance of a genuine and representative Latin American philosophy concerning the Latin people’s identity formation paradigm, since its investigation is seen as a relevant epistemological field. Yet, anthropological, social and political issues have been carefully and deeply studied by the authors throughout this thesis. Therefore, the context of the Latin American (Americanista) Philosophy and its cultural, historical and philosophical invisibility is going to be analysed, mainly within Zea(1969) and Dussel (1971) philosophical perspectives, in order to demonstrate arguments which can provide a better understanding of this phenomenon. The possibility of an authentic Latin American (Americanista) thought supported by the pedagogy for liberation based on Dussel (1971) and Freire (1996) is also going to be addressed. Finally, the contribution of the national curricular documents and teaching materials – in Philosophy teaching in Brazil – are going to be analysed too, in order to reflect upon the role of education in the construction of a genuine Latin American (Americanista) thought.